2000
DOI: 10.1074/jbc.275.6.3984
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Subunits of the Oligosaccharyltransferase Complex in the Endoplasmic Reticulum

Abstract: Membrane proteins of the endoplasmic reticulum (ER) may be localized to this organelle by mechanisms that involve retention, retrieval, or a combination of both. For luminal ER proteins, which contain a KDEL domain, and for type I transmembrane proteins carrying a dilysine motif, specific retrieval mechanisms have been identified. However, most ER membrane proteins do not contain easily identifiable retrieval motifs. ER localization information has been found in cytoplasmic, transmembrane, or luminal domains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 52 publications
(61 reference statements)
3
31
0
Order By: Relevance
“…However, if it is co-expressed with ribophorin I, ribophorin II, or chimeras that contain domains of ribophorin I, ribophorin II, and the Tac antigen (interleukin-2 receptor ␣ chain precursor), which by themselves do not exit from the ER, OST48ss could be retained in the ER. Similar observations were found with ribophorin II (24,25). Therefore, it is possible that ribophorin I, ribophorin II, and OST48 may play a critical role in maintaining the mammalian OT complex in the ER.…”
Section: Mechanistic Complexities Of Ot: Structural Integrity and Corsupporting
confidence: 85%
See 1 more Smart Citation
“…However, if it is co-expressed with ribophorin I, ribophorin II, or chimeras that contain domains of ribophorin I, ribophorin II, and the Tac antigen (interleukin-2 receptor ␣ chain precursor), which by themselves do not exit from the ER, OST48ss could be retained in the ER. Similar observations were found with ribophorin II (24,25). Therefore, it is possible that ribophorin I, ribophorin II, and OST48 may play a critical role in maintaining the mammalian OT complex in the ER.…”
Section: Mechanistic Complexities Of Ot: Structural Integrity and Corsupporting
confidence: 85%
“…However, deletion of this segment did not lead to a significant growth defect in yeast cells, suggesting that it does not function to retain the OT complex in the ER (20,23). In contrast, in the mammalian system it has been shown (24,25) that when one of the components of OT complex was mislocated by mutations in its own retention signal, it could be retained in the ER via its interaction with other subunits. Three mammalian OT subunits, ribophorin I, ribophorin II, and OST48 (mammalian homologs of yeast Ost1p, Swp1p, and Wbp1p, respectively), were found to contain specific ER localization signals.…”
Section: Mechanistic Complexities Of Ot: Structural Integrity and Cormentioning
confidence: 99%
“…Studies from a number of KKXX motif-containing ER molecules indicate that how far down the secretory pathway KKXX mutants escape varies widely in the range from plasma membrane expression to limited increase in post-ER compartments (18,36). This variation is largely due to differences in interaction with other ER retention proteins and the maturation process in its own, e.g., glycosylation (37). However, most of the studied ER proteins with KKXX mutations have been shown to increase their distribution in post-ER compartments (18,37).…”
Section: Discussionmentioning
confidence: 99%
“…This variation is largely due to differences in interaction with other ER retention proteins and the maturation process in its own, e.g., glycosylation (37). However, most of the studied ER proteins with KKXX mutations have been shown to increase their distribution in post-ER compartments (18,37). Although tpn is an ER residential molecule, a proportion of tpn is detected in the Golgi (4) and tpn interacts with an ER export receptor (38), supporting the notion that tpn could escape from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Because no differences were observed in the localization and/or retention of the membrane-bound SEP/SEP ⌬ , only the findings with SEP ⌬ are presented. Several reports have shown that the cytoplasmic domain of type II membrane proteins determine ER localization (15)(16)(17). Thus, we first analyzed a chimeric protein S/S/E (SEP ⌬ cytoplasmic, SEP ⌬ transmembrane, and bECE-1b luminal, Fig.…”
Section: The Luminal Domain Of Sep/sep ⌬ Determines Its Er Localizatimentioning
confidence: 99%